2008
DOI: 10.7863/jum.2008.27.12.1673
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Renal Volume Measurements Obtained by a 3-Dimensional Sonographic Transducer With Matrix Electronic Arrays

Abstract: Objective. The purpose of this study was to examine the feasibility of 3-dimensional (3D) sonography using a matrix array transducer to measure renal volume. Methods. One hundred consecutive patients with a normal serum creatinine level and kidney appearance on computed tomography (CT) performed within 2 months before sonography were enrolled in this study. Two hundred individual renal volumes were blindly obtained by the ellipsoid formula, the stacked ellipse method, the voxel count method using routine 2-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
0
26
0
2
Order By: Relevance
“…Since serum Cys-C levels are frequently superior to serum creatinine levels as an index of renal function [95] with some limitations, it might be introduced as a marker of renal function and follow-up in these patients. Moreover, low renal volume detected by ultrasound measurement of renal length [96, 97] and 3-dimensional ultrasound volume [98, 99] might represent suitable parameters of reduced renal reserve in newborns and children. Scintigraphic measurement may provide a comparison of the renal reserve between kidneys and their relative variation by age in congenital unilateral reduced renal reserve [63].…”
Section: Detection Of Reduced Nephron Reservementioning
confidence: 99%
“…Since serum Cys-C levels are frequently superior to serum creatinine levels as an index of renal function [95] with some limitations, it might be introduced as a marker of renal function and follow-up in these patients. Moreover, low renal volume detected by ultrasound measurement of renal length [96, 97] and 3-dimensional ultrasound volume [98, 99] might represent suitable parameters of reduced renal reserve in newborns and children. Scintigraphic measurement may provide a comparison of the renal reserve between kidneys and their relative variation by age in congenital unilateral reduced renal reserve [63].…”
Section: Detection Of Reduced Nephron Reservementioning
confidence: 99%
“…According to the literature, the 3D technique appears to produce an underestimation of renal volume [19], even though this underestimation is lower than that of the ellipsoid formula [19]. In our study conducted on 49 patients and a total of 98 kidneys, 3D-US revealed higher values compared with MSCT in 11 cases only (11%), with a mean difference of 17 ml; in the remaining 87 cases (89%), MSCT yielded higher values (mean difference 24 ml).…”
Section: Discussionmentioning
confidence: 95%
“…Tuttavia, nonostante il riconoscimento di questa sottostima, la metodica ecografi ca è stata considerata comunque adeguata alle necessità cliniche in quanto non risulta fondamentale il valore assoluto del volume renale ma la sua variazione nel tempo. Da quanto noto in letteratura, anche la tecnica 3D appare caratterizzata da una sottostima del valore del volume renale [19], ma tale sottostima risulta inferiore a quella che si verifi ca con la tecnica dell'ellisoide [19]. Dal nostro studio su 49 pazienti per un totale di 98 reni, l'ecotomografi a 3D ha fornito un valore superiore a quello della TCMS in soli 11 (11%) casi con differenza media pari a 17 ml); nei restanti 87 (89%) casi, la TCMS ha fornito un valore superiore (differenza media pari a 24 ml).…”
Section: Discussionunclassified
See 2 more Smart Citations